Neoadjuvant Chemotherapy in Breast Cancer Patients Induces miR‐34a and miR‐122 Expression. Issue 2 (February 2015) - Frères, Pierre; Josse, Claire; Bovy, Nicolas; Boukerroucha, Meriem; Struman, Ingrid; Bours, Vincent; Jerusalem, Guy
<x xml:space="preserve">Abstract</x> Circulating microRNAs (miRNAs) have been extensively studied in cancer as biomarkers but little is known regarding the influence of anti‐cancer drugs on their expression levels. In this article, we describe the modifications of circulating miRNAs profile after neoadjuvant chemotherapy (NAC) for breast cancer. The expression of 188 circulating miRNAs was assessed in the plasma of 25 patients before and after NAC by RT‐qPCR. Two miRNAs, miR‐34a and miR‐122, that were significantly increased after NAC, were measured in tumor tissue before and after chemotherapy in 7 patients with pathological partial response (pPR) to NAC. These two chemotherapy‐induced miRNAs were further studied in the plasma of 22 patients with adjuvant chemotherapy (AC) as well as in 12 patients who did not receive any chemotherapy. Twenty‐five plasma miRNAs were modified by NAC. Among these miRNAs, miR‐34a and miR‐122 were highly upregulated, notably in pPR patients with aggressive breast cancer. Furthermore, miR‐34a level was elevated in the remaining tumor tissue after NAC treatment. Studying the kinetics of circulating miR‐34a and miR‐122 expression during NAC revealed that their levels were especially increased after anthracycline‐based chemotherapy. Comparisons of the plasma miRNA profiles after NAC and AC suggested that chemotherapy‐induced miRNAs originated from both tumoral and non‐tumoral compartments. This study is the first to demonstrate that NAC specifically induces miRNA expression in plasma and tumor tissue, which might be involved in the anti‐tumor effects of chemotherapy in breast cancer patients. J. Cell. Physiol. 230: 473–481, 2015. © 2014 Wiley Periodicals, Inc.